Peningkatan Profesionalitas Guru Dalam Pengelolaan Hasil Belajar Melalui Teknik “Respect, Empathy, Observation, And Group Discussion” Sdn Tampojung Pregi Kecamatan Waru Kabupaten Pamekasan Tahun Pelajaran 2019/2020 - Mohammad Ruslan (Departement of Mathematics Education, 2023)
One quite effective way is through the application of Respect, Empathy, Observation, And Group Discussion techniques. Therefore, it is necessary to carry out school action research to prove that through the application of learning to write poetry using the Respect, Empathy, Observation, And Group Discussion technique can improve student learning outcomes and activities in learning Indonesian. This study used three rounds of action research. Each round consists of four stages: design, activity and observation, reflection, and revision. The target of this study were fifth grade students at SDN Tampojung Pregi, Waru District, Pamekasan Regency. The data obtained were in the form of daily test results, observation sheets of teaching and learning activities. Based on the results of school action research it can be interpreted (1) The application of learning using Respect, Empathy, Observation, And Group Discussion techniques can increase the activity of the teaching and learning process, (2) From the observations it was revealed that there was an increase in student activity which in cycle I was only average flat. an average of 69% to 74% in the second cycle and 85% in cycle III, (3) the ability in group discussions also made significant progress. This can be seen from already getting used to learning in groups, (4) Student activities in groups reach perfection after cycle III. This can be seen from the increase in student activity reaching 85%, (5) Student mastery of learning material shows an increase. This can be illustrated by the average daily test result (the average daily test for learning I without using the techniques of Respect, Empathy, Observation, and Group Discussion 5.48 to 6.53 (daily test II) and 7.33 (daily test III) after using the learning techniques of Respect, Empathy, Observation, and Group Discussion, (6) Through learning using the Respect, Empathy, Observation, and Group Discussion techniques, students build their own knowledge, find steps in finding solutions to a material that must be mastered by students, both individually and in groups, and (7) By learning to use Respect, Empathy, Observation, And Group Discussion techniques, learning Indonesian basic competence in writing poetry is more enjoyable.